Glow discharge polymerization of porous polyaniline film on argon sputtered silicon (100) - Lozada, Lou Serafin M.; Trinidad, Lorele C.; Ramos, Henry J. (2010)
This paper explores the formation of porous polyaniline film on modified silicon substrate by plasma-induced polymerization of monomer precursor aniline. Silicon surface was sputtered with argon plasma to form a porous layer. Aniline was introduced into the chamber and deposited on the silicon surface at different stages - before, during, and after argon sputtering of substrate. It was observed that the proportion of argon in the gas phase during plasma-induced polymerization affected the smoothness of the film formed. Smooth and even film was achieved with low concentrations of argon in the chamber. These were also observed for films deposited on unmodified silicon surface. At higher concentration of argon during polymerization, pore formations were present but not as pronounced as in argon sputted silicon. Polyaniline film formed through this method was smooth and had filled pores. However, polyaniline formed on porous silicon appeared porous as well. The deposited film followed the contour and shape of the silicon substrate.
Keywords: Polymerization